THE EFFECT OF JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT ON JOB ROTATION WITH EMPLOYEE ENGAGEMENT AS AN INTERVENING VARIABLE IN THE REGIONAL APPARATUS ORGANIZATION (OPD) OF CILEGON CITY - Sahroni, Sahroni; Sutisna, Sutisna; Sari, Gema Ika (Yayasan Education and Social Center, 2025)
One of the challenges faced by the Cilegon City Regional Government is the increasing resistance to job rotation. The main factors causing this resistance include low compensation due to operational budget limitations when employees are transferred to other agencies, placement of transfers at echelon II, III, and IV levels that do not match their educational background, and psychological aspects arising from the change of regional head. This study aims to analyze the role of job satisfaction, organizational commitment, and employee engagement in influencing job rotation. This study uses a descriptive causal design with a quantitative approach according to the positivist paradigm. Data were collected through research instruments and analyzed using statistical-based hypothesis testing. The results show that job satisfaction has a significant positive effect on employee engagement with a coefficient value of 0.616, a t-statistic of 5.544, and a p-value of 0.000. In addition, job satisfaction and organizational commitment have been shown to have a positive effect on job rotation. Employee engagement also functions as a mediating variable that strengthens the relationship between job satisfaction and organizational commitment to job rotation. Thus, the higher the level of job satisfaction and organizational commitment, the higher the employee engagement, which ultimately encourages more effective implementation of job rotation in the Cilegon City Regional Apparatus Organization (OPD)